Bone tumors - (:unkn) unknown (Springer International Publishing, 2015)
Musculoskeletal tumors are uncommon and when they occur usually benign. The diagnosis of these tumors is often delayed. Early detection of a malignant tumor may not only make the difference between life and death, but also may allow for successful limb salvage surgery rather than amputation of the limb. This chapter will cover general principles of musculoskeletal tumor diagnosis and treatment, and the common individual entities. © Springer International Publishing Switzerland 2016.